Effect of hip CPM on gross motor function and development of the hip joint: a single-center randomized controlled study on spastic cerebral palsy children with hip dysplasia - Wang, Lulu; Zhang, Nuochen; Fang, Liwei; Cui, Zhenzhen; Niu, Huihui; Lv, Fuli; Hu, Dayong; Wu, De (Frontiers in Pediatrics, 2023)
Objective：To investigate the effectiveness of hip continuous passive motion (hCPM) on the hip development at skeletal maturity and gross motor function for spastic cerebral palsy children with hip dysplasia. Methods：Prospective case-control research of hCPM with goal-directed training vs. merely goal-directed training. On the basis of goal-directed training, the hCPM group used the hip joint CPM instrument (the external fixator was connected to the power device to make the hip joint carry out continuous passive movement) for 40-60 minutes, twice a day, five times a week, and continuous training for 8 weeks simultaneously; The control group only used goal-directed training for 8 weeks.Functional outcomes pertaining to the affected hip joints were assessed via GMFM, MP, AI, and HHS at the time of enrollment and the end of the intervention. Results：The case-control research included 65 participants (mean age=46.20 months, standard deviation [SD]=17.09 months; Gross Motor Function System level: III=41, IV=24) who were randomly selected to the hCPM (n=45) or control group (n=20). No differences were found in baseline (acquisition phase) GMFM, MP, AI, or HHS[t=-1.720, P=0.090; t*=1.836, P*=0.071; t#=-1.517，P#=0.139; t*=-1.310, P*=0.195; t#=-1.084, P#=0.097; t=-1.041, P=0.301]. At the 8-week follow-up, GMFM, MP, AI, and HHS were significantly improved over baseline in hCPM groups[ hCPM group: t=18.59, 20.172*, 40.291#, 16.820*, 32.900#, 28.081; P＜0.001]. Between-group differences at 8-week follow-up times points favored the hCPM group for GMFM (t=-2.637, P=0.011), MP (t*=2.615, P*=0.014; t#=3.000，P#=0.006), AI (t*=2.055, P*=0.044; t#=2.223，P#=0.030), HHS(t=-4.685, P＜0.001)[*left side;#: right side]. Conclusion：Spastic cerebral palsy children with hip dysplasia achieved meaningful functional improvement after 8 weeks goal-directed training with hCPM therapy. Keywords: Spastic cerebral palsy; Hip dysplasia; Hip continuous passive motion; Goal-directed training Abbreviations: hCPM, hip continuous passive motion; GMFM, Gross Motor Function Measure; MP, migration percentage; AI, acetabular index; HHS, Harris hip functional score.